SYNTHESIS OF 4-(3,4-DIMETOXY-PHENYL)-3-BUTENE-2-ON AND ACTIVITY IT’S TEST AS A FRUIT FLIES ATRACTANT - Deni Pranowo; Suputa Suputa; Tutik Dwi Wahyuningsih (Universitas Gadjah Mada, 2006)
4-(3,4-dimethoxyphenyl)-3-buten-2-on has been synthesized from veratraldehyde and acetone via aldol condensation. The reaction was performed at room temperature under basic condition for 24 hours to give brown solid of product (m.p 64-6 5oC) in 73.7% yield. Veratraldehyde itself was produced from alkylation of vanillin by the use of dimethylsulfate. The structure of the products was analyzed by FTIR, 1H NMR and GC-MS. Activity test of 4-(3,4-dimethoxyphenyl)-3-buten-2-on as an attractant was carried out in Sleman, Bantul and Kulon Progo with methyl eugenol as a reference. The result showed that 4-(3,4-dimethoxyphenyl)-3-buten-2-on was inactive compound as a fruit flies attractant and some of fruit flies, i.e. Bactrocera papayae, B. carambolae, B. umbrosa and B. abdolonginqua was found on the test area.